Study of Proportional and Absolute Volume of Placental Parenchyma and Non-Parenchyma Between Normal Pregnant and Preeclamptic Women - Kishwara, S; Nurunnabi, ASM; Begum, M; Ahmed, R; Ara, S (Journal of Dhaka Medical College, 2010)
Context: The changes in volume of the placenta and its internal components are evident in different maternal diseases like preeclampsia. Postnatal examination of the placenta is an important method for assessing maternal and fetal condition in antenatal and perinatal periods and enriching practical knowledge. Study design: Cross-sectional descriptive type. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka from August 2005 to June 2006. Materials & Methods: 54 human placentae from Bangladeshi women were collected from the Department of Obstetrics & Gynaecology of Dhaka Medical College Hospital and Sir Salimullah Medical College Hospital, of which 27 from normal uncomplicated pregnancies (control group) and another 27 from pregnancies complicated by preeclampsia (study group) where the patients were normotensive previously. Results: Both the proportional and absolute volume of placental parenchyma were found lower in preeclamptic women than those of normal pregnant women (P<0.001). But only in the absolute volume of non-parenchyma of the placenta, there was difference in between two groups (P<0.001), no difference found in relative volume (P>0.50). Key words: placenta; volume; parenchyma; non-parenchyma; preeclampsia. DOI: 10.3329/jdmc.v17i2.6587 J Dhaka Med Coll. 2008; 17(2) : 78-82